Discourse and silencing : representation and the language of displacement - Thiesmeyer, Lynn (Discourse approaches to politics, society, and culture ;, 2003)
Silencing is not only a physically coercive act. It is also an act of language involving forms of selection, representation and compliance. Discourse and Silencing weaves together theories and examples of discourse from different disciplines in order to put forward a theory of silencing in language: that discursive systems filter, represent and displace types of knowledge into other forms of expression. Each chapter of the book analyses examples of silencing through discourse in various social and political fields. The examples cover courtroom trials, government censorship, domestic violence, m.